Austria 2011 - Blanco, Angeli Jane Aspiras (2012)
"Families have the unique position of serving as links between individuals and the larger society. It is through the family's functions of reproduction, biological and psychological support, and training for social participation and citizenship, that society is able to elicit from an individual his contribution. (Taylor, 1997). Families are also unique in providing continuity of social life. It is major agent in the transmission of culture, political and societal awareness and class consciousness. (Taylor, 1997). A story of consanguinity, disconnection and frivolity, Austria 2011 follows the contemporary bourgeois Austria clan during their reunion as they are left enmeshed in a web of self-inflicted pain and pretense. It is primarily a story of personal issues, old wounds and news revelation, while also a commentary on the superficiality of the bourgeois culture and a confirmation of the universal truth that, bittersweet as it may seem, family conflicts defy social class."